2012
DOI: 10.1371/journal.pone.0035548
|View full text |Cite
|
Sign up to set email alerts
|

Testing an Emerging Paradigm in Migration Ecology Shows Surprising Differences in Efficiency between Flight Modes

Abstract: To maximize fitness, flying animals should maximize flight speed while minimizing energetic expenditure. Soaring speeds of large-bodied birds are determined by flight routes and tradeoffs between minimizing time and energetic costs. Large raptors migrating in eastern North America predominantly glide between thermals that provide lift or soar along slopes or ridgelines using orographic lift (slope soaring). It is usually assumed that slope soaring is faster than thermal gliding because forward progress is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
102
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 30 publications
4
102
0
1
Order By: Relevance
“…Therefore, eagles living in conditions suited to orographic soaring might incur greater energetic costs. Migration of golden eagles is faster and more energetically efficient when thermal soaring combined with gliding is used compared to orographic soaring (Duerr et al., 2012), and migratory flight has been positively correlated with weather conditions promoting thermal uplift, suggesting that eagles preferentially travel when conditions favor thermal soaring over orographic soaring (Duerr et al., 2015). Terrain ruggedness has been identified as an important determinant of increased heart rate in turkey vultures Cathartes aura due to its effect on decreasing the spatiotemporal predictability of uplift (Mandel, Bildstein, Bohrer, & Winkler, 2008), again potentially representing the cost associated with soaring in highly variable mountainous conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, eagles living in conditions suited to orographic soaring might incur greater energetic costs. Migration of golden eagles is faster and more energetically efficient when thermal soaring combined with gliding is used compared to orographic soaring (Duerr et al., 2012), and migratory flight has been positively correlated with weather conditions promoting thermal uplift, suggesting that eagles preferentially travel when conditions favor thermal soaring over orographic soaring (Duerr et al., 2015). Terrain ruggedness has been identified as an important determinant of increased heart rate in turkey vultures Cathartes aura due to its effect on decreasing the spatiotemporal predictability of uplift (Mandel, Bildstein, Bohrer, & Winkler, 2008), again potentially representing the cost associated with soaring in highly variable mountainous conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, orographic uplift concentrates along ridgelines and is thought to provide favorable conditions for the long‐distance autumn migration of large soaring birds (Brandes & Ombalski, 2004; Bohrer et al., 2012. But see: Duerr et al., 2012, 2015; Katzner et al., 2015). Mountainous areas are usually associated with high uplift availability, owing to their ability to generate orographic uplift even in low‐wind conditions or cool temperatures (Shepard & Lambertucci, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…‡ Degree Celsius consistent sources of lift than vertically deflected air along the ridgelines. Duerr et al (2012) suggested that overall migration speed would be slower, and movement trajectories more constrained to underlying topography, for birds utilizing slope soaring instead of thermals. However, the high and consistent winds during this migratory period in the eastern Rockies may benefit eagle passage because movement rates were higher and more consistent during periods in the fall when slope soaring was used, e.g., during high winds.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, both early morning and late afternoon passage were low under weak winds, typically with NE winds; even though passage did increase by midday under these conditions, overall passage on these days was much lower than seen during high-wind conditions. Under such low-wind conditions, birds may not be able to initiate movement until thermal activity on the ridgelines, which is not present when strong winds dissipate warm, rising pockets of air (Shamoun-Baranes et al 2003, Ákos et al 2008, Chevallier et al 2010, Duerr et al 2012, begins to peak at midday. However, whether eagles respond to strong winds by taking flight earlier in the day or to weak winds and thermal activity by concentrating movement later in the morning, both scenarios attest to the overwhelming importance of documenting spatial and temporal patterns of movement to identify conditions of collision risk.…”
Section: Discussionmentioning
confidence: 99%
“…Dans l'est de l'Amérique du Nord, les oiseaux de proie utiliseraient, entre autres, les Appalaches Introduction L'observation et le suivi de la migration des oiseaux de proie ont débuté il y a déjà plus d'une trentaine d'années dans plusieurs sites de l'Amérique du Nord (Bieldstein et Klem, 2001; Hawk Migration Association of North America, 2014). Les ornithologues prennent souvent plaisir à observer la migration abondante des oiseaux de proie lors de la venue de l'automne comme c'est le cas à Tadoussac, Cape May ou Hawk Mountain (Berthiaume, 2006;Dickey, 2012;Buidin, 2014). Toutefois, plusieurs sites sont également exceptionnels pour effectuer l'observation de leur migration printanière.…”
unclassified